The impact of brand equity, service quality, and organizational performance on public trust in zakat institutions: evidence from Indonesia - Edy Junaedi; Johan Budiman; Irwan Maulana; Aisyah Azzahra; AR Haikal Alkanz (Proceeding of National Conference on Accounting & Finance, 2026)
With an emphasis on the functions of organizational performance, service quality, and brand equity, this study attempts to explore the factors that influence public confidence in Indonesian zakat institutions. A survey questionnaire was used in a quantitative manner. Information was gathered from Indonesian zakat institutions' donors and recipients. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS 3.0 was used to examine the study model. The findings show that public trust is significantly positively impacted by organizational performance (β = 0.198, p < 0.01) and service quality (β = 0.771, p < 0.001). Remarkably, it was discovered that public trust was not significantly impacted by brand equity (β = -0.148, p = 0.568). With a significant explanatory power, the model accounts for 63.7% of the variation in public trust. In order to establish and maintain public trust, managers of zakat institutions should place a high priority on investments in excellent service delivery and strong internal governance, including accountability and transparency. Without these fundamental components, brand-building initiatives are insufficient. This study challenges the notion that brand equity has a direct impact on trust in religious charitable contexts by highlighting service quality as the most important driver of trust in Islamic social finance institutions.